Enhancement of machinability of nickel based alloy - inconel 718 by induction preheating in end milling using ceramic inserts - Mokhtar, Suhaily; Amin, A. K. M. Nurul; Patwari, Anayet Ullah; A. Azhar, A. Hazim; A. R., Zulkhari (2010)
Unique combinations of high strength properties maintained at elevated temperature and high resistance to chemical degradation have made Nickel based alloy, Inconel 718 suitable for application as aerospace components. However, the same properties are responsible for very poor machinability of the material, as Inconel is one of the most difficult to cut materials. The main reason for poor machinability is generation of high heat during machining which lead to premature failure of the tool due to plastic deformation and diffusion. Uncoated and coated tools have been found to be not efficient in cutting this materials and the application of preheated resulted in not significant improvement in their machinability. PCD tools are not recommended for machining this material since it contains iron which acts as a catalyst to convert diamond into graphite at temperatures in excess of 700 0C. PCBN tools are very costly and also did not show very good performance in machining Inconel 718. Ceramic tools have proved to have performed well in machining the material. However, there was so far no work performed performance of ceramic tools in machining Inconel 718 using preheated technique. Since ceramic tools can perform under high temperatures, it was expected that preheated machining using ceramic tools would desired results. In this research work induction heating technique in combination of the application of ceramic tools was adopted as one of the machining techniques in order to improve the machinability of the material. The effect of preheated machining of Inconel 718 has been analyzed in terms of tool wear, surface roughness and chip formation. The advantages of preheated machining are demonstrated by appreciable increase in tool life, better surface roughness values and improved chip formation compared to room temperature machining.